Pendidikan Estetika Melalui Seni Budaya - Siti Mutmainah, (Pendidikan Sekolah Dasar, 2009)
Education is essentially the conscious effort to develop the personality and abilities of students within and outside of school and lasts a lifetime. Aesthetic experience began to expire/has expired, it turns out mans search for ways to immortalize it or raises it again. Arts in English: Art, from the birth of arts, artists (skills) to show any act committed intentionally and purposefully referring to what is beautiful or beauty (aesthetics). The artwork is the work of human culture. Culture is the origin of the word intellect and power. Budi means spiritual tool that is a blend of reason and feelings to draw good & bad. Power is an attempt to achieve something. The role of teachers in aesthetic education through arts and culture is a teacher must have stock in the learning activities of arts and culture in theory, knowing the correct rules in directing, guiding and motivating children in performing arts activities.